Identifying the role of exogenous amino acids in catalyzing lignocellulosic biomass into humus during straw composting. (November 2021) - Zheng, Guangren; Liu, Chengguo; Deng, Ze; Wei, Zimin; Zhao, Yue; Qi, Haishi; Xie, Xinyu; Wu, Di; Zhang, Zhechao; Yang, Hongyan
Graphical abstract: Highlights: Exogenous amino acids promoted lignocellulose degradation and humus synthesis. Amino acids promoted humus synthesis by acting as precursors. Amino acids promoted humus synthesis by affecting bacterial communities. Key bacteria involved in humus synthesis were identified. The metabolic function of bacterial community was analyzed. Abstract: This study was aimed at exploring the mechanism of promoting humus formation by the addition of exogenous amino acids. Amino acids not only participated in the synthesis of humus directly as precursors, but also changed the functions of bacterial communities. The composition and diversity of bacterial community changed with the addition of amino acids. The ability of bacterial community to degrade lignocellulose was enhanced, which provided precursors for humus synthesis. The key bacteria for humus formation and organic matter transformation were identified using random forests. These bacteria showed growth advantage with the addition of amino acids. The results showed that exogenous amino acids tended to transform organic matter and synthesize humus. Variance partitioning analysis confirmed that the bacterial community was the driving force of humus synthesis. These results were further verified by the structural equation model. These findings provided new ideas and understanding for straw waste composting.